Value of the prognostic nutritional index (PNI) in patients with newly diagnosed, CD5‐positive diffuse large B‐cell lymphoma: A multicenter retrospective study of the Huaihai Lymphoma Working Group. Issue 19 (6th August 2022) - Ma, Sha; Zhang, Bingpei; Lu, Tianyi; Li, Dashan; Li, Tianci; Shen, Ziyuan; He, Chenlu; Wang, Ying; Li, Bingzong; Zhang, Hao; Gu, Weiying; Wang, Chunling; et al.
Abstract : Background: CD5‐positive diffuse large B‐cell lymphoma (DLBCL) is a clinically rare subtype of DLBCL with aggressive clinical manifestations and a poor prognosis. It has been demonstrated that the prognostic nutritional index (PNI), an indicator of nutritional status and systemic inflammation, is a significant prognostic factor for several types of lymphoma. The objective of this multicenter retrospective study was to explore the prognostic value of the PNI in patients with CD5‐positive DLBCL. Methods: In total, 207 patients with CD5‐positive DLBCL were recruited from 11 centers of the Huaihai Lymphoma Working Group. Maximally selected rank statistics analysis was used to identify optimal cutoff points for the PNI. A Cox proportional hazards model was used for univariable and multivariable analyses. Kaplan–Meier curves were used to calculate survival rates and draw survival curves, and the log‐rank test was used to compare differences between groups. Results: The median age at diagnosis was 61 years, and the 5‐year overall survival rate was 47.5%. According to the maximally selected rank statistics analysis, a score of 49.7 was the optimal cutoff point for the PNI. Subgroup analysis showed that the PNI could re‐stratify patients in BCL‐2–negative, MYC‐negative, high‐intermediate–risk and high‐risk International Prognostic Index, BCL‐6–positive and BCL‐6–negative, high Ki‐67 score (≥0.9), Ann Arbor stage III/IV, Eastern Cooperative Oncology Group performance status ≥2, and germinal center B subgroups. Multivariable analysis revealed that PNI, age, Eastern Cooperative Oncology Group performance status, albumin level, and red blood cell count were independent prognostic factors for CD5‐positive DLBCL. Conclusions: The PNI was a significant prognostic indicator for CD5‐positive DLBCL and was able to re‐stratify the prognosis for clinicopathologic subgroups of patients with CD5‐positive DLBCL. Abstract : PNI was a significant prognostic indicator for CD5+ DLBCL patients and could re‐stratify the prognosis in clinicopathological subgroups of CD5+ DLBCL.